Hijrat Movement: First Political Case in the Modern History of Sindh (Al-Qamar, 2023)
The Hijrat movement was the struggle of the underprivileged class, which unfortunately failed to achieve its goal. Besides, it began for the restoration of the Ottoman Empire in support of the hands of Indian Khilafat, between those people who migrated towards the place of Dar-ul-Islam selecting Afghanistan are still clandestine. However, the present study raises the question of forgotten people who migrated to Afghanistan by vending their apartments and properties, proving the first political case in modern Sindh's history. The proposed research involved secondary data from different reliable sources, i.e., digital libraries, Journals, books, and the rest. The researcher applied the historical approach to the study. Besides, This study vests output to literature and history readers as well as the godsends following the research sources in writing new instances of the modern history of Sindh. The study uncovers that the Hijrat movement has significantly contributed to the contemporary history of Sindh by wooing a scientific knowledge-based method. The study touches on the core of the cream contribution equipping facts and figures. It helps to eradicate fictionalized premises from the modern history of Sindh in light of the Hijrat movement as the first case of political history. The study would help research other aspects of the contemporary history of Sindh for the political history and domain of Sindh. The introspection also suggests implicating Sindh's history, and the findings play a vital role in highlighting the contribution of migrants. The research outcomes would further open the windows of future research into the different factors of history.
Keywords: Case of Sindh; Modern Political History of Sindh; Hijrat Movement